The financial toxicity of cancer: unveiling global burden and risk factors – a systematic review and meta-analysis - Addisu Getie; Alemu Birara Zemariam; Befkad Derese Tilahun; Ribka Nigatu Haile; Tegene Atamenta Kitaw; Molla Azmeraw Bizuayehu (BMJ Global Health)
Background Cancer, a major global health challenge, not only threatens lives but also imposes severe financial burdens, known as ‘financial toxicity’. This strain extends beyond treatment costs to include indirect expenses like lost income and out-of-pocket payments. Despite its urgency, global insights remain fragmented, often limited to specific regions with inconsistent findings. This systematic review and meta-analysis aims to provide a comprehensive overview of cancer-related financial toxicity and identify key risk factors contributing to this burden.Methods We conducted a systematic review and meta-analysis, searching databases like Medline, Web of Science, PubMed, Scopus, International Scientific Indexing and Google Scholar for peer-reviewed observational studies. Data were extracted into Microsoft Excel 2021, and study quality was assessed using the Joanna Briggs Institute critical appraisal tool. Statistical analysis was performed using STATA V.17, with catastrophic health expenditures (CHEs) pooled via a random-effects model. Heterogeneity was explored to understand variations in study outcomes. Subgroup and sensitivity analyses were conducted to assess individual study impacts, while publication bias was evaluated using Begger and Egger’s tests. Univariate meta-regression analysis determined the impact of study-level covariates on CHE estimates.Results This analysis included 35 observational studies, covering 428 373 patients with cancer. The pooled prevalence of CHE was 56.1% (95% CI 48.3% to 63.8%). Key risk factors included large family size, low income, lack of health insurance, longer disease duration, older age and multiple treatments. Higher education levels were associated with reduced CHE risk.Conclusion Over half of patients with cancer (56.1%) face catastrophic health expenditures, highlighting a severe financial burden. Addressing this issue requires expanding health insurance, providing financial support and ensuring affordable cancer care. Improving education access can also reduce CHE risk among patients with cancer.